Sound and mechanised compositional verification of input‐output conformance. (14th May 2013) - Sampaio, Augusto; Nogueira, Sidney; Mota, Alexandre; Isobe, Yoshinao
SUMMARY This paper mechanises conformance verification in the setting of the CSP process algebra. The verification strategy is captured by a theorem stated as a process refinement expression, which can be verified by a model checker such as FDR. The conformance relation, cspio, distinguishes input and output events. The process algebraic framework of CSP is used to address compositional conformance verification by establishing compositionality properties for cspio with respect to the CSP operators. Although cspio has been defined in the standard CSP traces model, one can address quiescence situations using a special output event, in which case it is formally established that cspio is equivalent to Tretmans ioco. All the results have been mechanically proved using the CSP‐Prover. The proposed testing theory has been adopted in an industrial context involving collaboration with Motorola, on testing mobile applications. Several examples and a case study are presented to illustrate the overall approach. Copyright © 2013 John Wiley & Sons, Ltd.